MODIFIKASI STICK KACANG TOLO DALAM PENINGKATAN KADAR HAEMOGLOBIN REMAJA PUTRI DI DESA SUGIHARJO - Suhartini; Juita Sari; Nila Hayati (Jurnal Keperawatan Priority, 2021)
Anemia is a health problem all over the world, especially in developing countries. It is estimated that 30% of the world's population suffers from anemia, and it occurs in many communities, especially adolescents and pregnant women. Anemia in young women is still quite high, according to the World Health Organization (WHO). The prevalence of anemia in Indonesia at 21.7%. This research is important to do because the problem of anemia in young women in the village is still an interesting topic to discuss. Currently, anemia is one of the main nutritional problems in Indonesia, especially iron-deficiency anemia, especially in adolescents. This type of research is Quasi-Experimental with pre and post-test design. The research location is in the village of Sugiharjo, Batang Kuis District, Kab. Deli Serdang. The population in this study were 307 people. The number of samples taken was 20% of the total population, namely 60 adolescents who suffer from anemia, representing 12 people in each hamlet. To obtain the sample, it was done by screening, namely checking the Hb level with a Hb level <12 mg/dl. The Wilcoxon test results are known as Sig. (2-tailed) is worth 0.000. Because the value of 0.000 is less than <0.05, it can be concluded that there is a difference between the modifying action of tolo nut stick and the increase in HB levels in adolescents. It is recommended for young women to consume more tolo nuts in increasing Hb levels